The naughty mole: a book about obedience (Educational Technologies Ltd Place of publication not identified, 2004)
"The Naughty Mole: A Book About Obedience" tells the story of a young mole who struggles with following the rules. Despite his parents' advice, the mole often disobeys and gets into trouble while digging tunnels too far from home. One day, his mischief leads him into danger, teaching him a valuable lesson about the importance of listening to others and following instructions. Through fun and engaging adventures, the book highlights the consequences of disobedience and emphasizes the importance of responsibility and making safe choices.